Extracellular synthesis of silver dimer nanoparticles using Callistemon viminalis (bottlebrush) extract and evaluation of their antibacterial activity. Issue 4 (20th April 2016) - Rahisuddin,; Akrema,
ABSTRACT: Green methods are powerful tools to minimize the use of toxic chemicals which are harmful to human beings as well as environment. The present study focuses on the use of aqueous extract of Callistemon viminalis (bottlebrush) leaves for the synthesis of silver nanoparticles. The extract was used as a bioreductant and the polyphenols and flavanoids present in extract are responsible for the reduction of Ag + ions to zero valent silver nanoparticles. The effect of concentration of Ag + ions and cetyltrimethylammonium bromide on the nanoparticles was examined. On increasing the concentration of stabilizer, different morphological nano-couples are formed. The successful formation of silver nanoparticles was demonstrated by using ultraviolet–visible, transmission electron microscope and scanning electron microscope. Transmission electron microscope image analysis showed wide size distribution having dimer nanoparticles of hexagonal-triangular, square-triangular, spherical-triangular, spherical-spherical square-spherical morphologies. The antibacterial activity of extract reduced silver nanoparticles against four strains viz. Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae and Salmonella typhimurium was evaluated by calculation of minimum inhibitory concentration and minimum bactericidal concentration. The results show that synthesized nanoparticles could inhibit the growth of various bacteria tested.